Professor Richard A. Jonas: exploring ways to improve brain development in children with congenital heart disease - He, Chao-Xiu (Melanie) (Journal of Thoracic Disease, 2015)
Professor Richard A. Jonas joined the staff of Children’s National Medical Center in September 2004 as the Chief of Cardiovascular Surgery, Co-Director of the Children’s Heart Institute and Cohen Funger Professor of Cardiac Surgery. He undertook his general surgical training at the Royal Melbourne Hospital in Melbourne Australia and subsequently his cardiothoracic surgical training at Royal Children’s Hospital in Melbourne and Green Lane Hospital in Auckland New Zealand. After fellowships at the Brigham and Women’s Hospital and Children’s Hospital Boston he was appointed to the Department of Surgery at Harvard Medical School in 1984. In 1994 Professor Jonas was appointed to the William E. Ladd Chair of Surgery at Harvard Medical School and became the Cardiovascular Surgeon in Chief at Children’s Hospital Boston.